Resilience and adaptive capacities in Cyclone Larry - Oloruntoba, Richard (2015)
The paper presents a theoretical overview of the concept of resilience. The overview comprises current understandings of resilience, and its main components: stress; adaptation; wellbeing; and resources. The paper also analyses the relationship between resources and their dynamic attributes; a network of adaptive capacities; and rapid adaptation after a disruption, ─ the key attribute of resilient systems. Community resilience is manifested in quick restoration of community functioning and individual welfare, and wellbeing after a disruptive event. The paper also argues that community resilience should be built long before an event from four categorisations of adaptive capacities: (1) wealth and economic development; (2) social networks and social capital; (3) effective information dissemination and communication systems as well as (4) technical knowledge and competence. The paper concludes by describing empirical case examples of some effective resilience strategies in the management of the Cyclone Larry disaster of March 20, 2006.